New Trends in Education: Computational Thinking and Its Role in Improving the Quality of School Human Resources - Anwar, Kasypul; Yuliansyah, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze how the application of computational thinking can affect students' analytical and problem-solving skills, as well as change the mindset of teachers from conventional teachers to innovators in one of the Junior High Schools in Banjarmasin City. This study uses a qualitative case study approach. Data were collected through observation, interviews, and documentation. Data were analyzed using thematic analysis techniques, including coding, identifying important themes, and interpretation in the context of computational thinking theory. Data triangulation was carried out by comparing the results of observations, interviews, and document analysis to ensure the validity of the findings. The results of the study indicate that computational thinking plays a significant role in improving students' technical and analytical skills and encouraging the transformation of teachers' mindsets towards a more innovative and adaptive approach to technology. In addition, this study also found that the implementation of computational thinking successfully addressed the gap in technology skills among students, thereby increasing educational equality. The implications of this study indicate that the application of computational thinking in the school curriculum can be an effective strategy to improve the quality of education in Indonesia. However, this study is limited to one location. It does not consider gender factors and variations in student backgrounds, so further research is needed with a wider scope to obtain a more comprehensive picture.